The theologian and the scientist of religion. Religiography regarding the interfaces between Science of Religion or Religiology and Theology in Brazil - Senra, Flávio (2016)
The interfaced debate between Science of Religion or Religiology and Theology in Brazil passes through the Religious Studies teaching production. This article, as a religiography approach, highlights some moments of a debate which started in a Seminar which took place in the year 2000 held at UFJF (Federal University of Juiz de Fora / Brazil) and continues until today. A character who followed that debateis the theologian and scientist of religion Afonso M. Ligorio Soares, who knew how to cohabit throughout his career in both  subareas of knowledge: Theology and Science of Religion. Soares’ position, besides reflecting clearly the specific approach of each area, points to the possible mutual collaboration. Considering the postgraduate production profile of teachers in the Science(s)of Religion(s) programs, besides the epistemological debate that should preside over that reflection, the current Graduate programs in Science of Religion and Theology area suggest that the Brazilian profile tends to recognize the interface between these two subareas in the field of Religious Studies in Brazil.